2012
DOI: 10.1073/pnas.1117984109
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric site-specific nucleases for genome editing

Abstract: Targeted manipulation of complex genomes often requires the introduction of a double-strand break at defined locations by site-specific DNA endonucleases. Here, we describe a monomeric nuclease domain derived from GIY-YIG homing endonucleases for genomeediting applications. Fusion of the GIY-YIG nuclease domain to threemember zinc-finger DNA binding domains generated chimeric GIYzinc finger endonucleases (GIY-ZFEs). Significantly, the I-TevI-derived fusions (Tev-ZFEs) function in vitro as monomers to introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 43 publications
3
63
1
Order By: Relevance
“…The I-TevI nuclease and linker domains have successfully been fused to four different DNA-binding architectures that are used in genome editing: zinc fingers (27), TALEs (29), meganucleases (30), and, as reported here, Cas9. An on-going debate in the genomeediting field centers on the ease of use (targeting range) versus specificity (off-target effects) of the various reagents, particularly for common laboratory manipulations of cell lines or model organisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The I-TevI nuclease and linker domains have successfully been fused to four different DNA-binding architectures that are used in genome editing: zinc fingers (27), TALEs (29), meganucleases (30), and, as reported here, Cas9. An on-going debate in the genomeediting field centers on the ease of use (targeting range) versus specificity (off-target effects) of the various reagents, particularly for common laboratory manipulations of cell lines or model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent repair would effectively delete the majority of the target site, preventing further cleavage. We previously created a dual nuclease termed MegaTev, a fusion of I-TevI to LAGLIDADG homing endonucleases (or meganuclease) (27,34,35). We showed that MegaTevs efficiently excises a 30-bp fragment from model DNA substrates in HEK293 cells (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations